Flipped learning's impact on junior high students' critical thinking in ecology topic: English - Diana Vivanti Sigit; Chesia Saranata Simanullang; Daniar Setyo Rini (Research and Development in Education (RaDEn), 2024)
Environmental issues have become a major global focus, with various stakeholders including practitioners, media, governments, and academics expressing concerns about ongoing environmental changes. To address these challenges, there is a need to enhance students' critical thinking skills to analyze ecological problems, equipping the next generation to understand and respond effectively. This study investigates the impact of the flipped learning model on middle school students' critical thinking skills in ecology topic. A quasi-experimental design was used, specifically a pretest-posttest nonequivalent control group design. Conducted at SMPN 216 Jakarta from January to June 2024, the research involved a sample of 72 students. Results analyzed with the non-parametric Mann-Whitney U test on gain scores indicate that the flipped learning model positively influences students' critical thinking skills in environmental issues, with an N-gain score of 0.49, categorized as medium. Therefore, this form of learning can be an effective alternative in improving students' critical thinking skills.